LncRNA CASC15 upregulates cyclin D1 by downregulating miR-365 in laryngeal squamous cell carcinoma to promote cell proliferation - Minhui Zhu; Caiyun Zhang; Peng Zhou; Shicai Chen; Hongliang Zheng (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background This study investigated the role of lncRNA CASC15 in laryngeal squamous cell carcinoma (LSCC). Methods This study included 58 LSCC patients. Both tumor (LSCC) and adjacent (within 3 cm around tumors) non-tumor tissues from 3 different sites of each patient were collected. CCK-8 assay was used to determine cell proliferation. The expression levels of proteins and mRNAs were determined by Western blotting analysis and qRT-PCRs, respectively. Results CASC15 was upregulated in LSCC and high expression levels of CASC15 predicted poor survival. In LSCC tissues, CASC15 was negatively correlated with miR-365 but positively correlated with cyclin D1. In LSCC cells, overexpression of CASC15 resulted in downregulation of miR-365 and upregulation of cyclin D1. Overexpression of miR-365 did not affect the expression of CASC15 but downregulated cyclin D1. Overexpression of Cyclin D1 did not affect the expression of miR-365 and CASC15. Overexpression of CASC15 and cyclin D1 led to promoted, while overexpression of miR-365 led to inhibited LSCC cell proliferation. In addition, overexpression of miR-365 reduced the effects of overexpression of CASC15. Conclusion Therefore, CASC15 upregulates cyclin D1 by downregulating miR-365 in LSCC to promote cell proliferation.